African Elephant Specialist Group Chair report/ Rapport du Groupe de Spècialistes de l'Eléphant d'Afrique - Ben Okita-Ouma; Rob Slotow (Pachyderm)
The last three years as the co-Chairs of the IUCN–SSC–African Elephant Specialist Group (AfESG/or referred to here as ‘the Group’) has been extremely busy but enjoyable and fulfilling. We feel indebted to our highly skilled and dedicated Group members who are always supportive and on their toes to promote our mission of conserving Africa’s elephants throughout their range. The Group’s input coupled with the unwavering support of the governments of range states, donors and multi-lateral agencies has enabled us to make significant strides as a Group in the last three years. We therefore begin the new 2021–2024 IUCN quadrennium on a strong footing. More so, we have strengthened our membership in numbers, additional skillsets and by building collegiality with governments and multi-lateral agencies. Our nine working groups and task forces are poised to tackle some thirty targets which we developed around our goals and aligned to the five key components of Assess, Plan, Act, Communicate and Network in the IUCN’s Species Strategic Plan.